EFFORTS TO GUIDE MARRIAGE PREPARATION FOR PERSONS WITH DISABILITIES AT THE RELIGIOUS AFFAIRS OFFICE OF PALEMBANG CITY - Agupta, Andreas; Huzaimah, Arne; Armasito, Armasito; Azhari, Ari (Usroh, 2025)
The mechanism for the Ijab Qobul in marriage by the groom is carried out verbally, however there are differences for grooms who have disabilities or for people with disabilities, where people with disabilities use several methods in carrying out the Ijab Qobul. The aim of this research is to find out what the efforts of the Religious Affairs Office (KUA) are in providing services for people with disabilities and what the guidance mechanism for preparing Ijab Qobul is for people with disabilities at KUA Ilir Timur 2, KUA Sukarami, KUA Ilir Barat 1, KUA Bukit Kecil. The research method used in this thesis is field research with qualitative research data. The data collection techniques are carried out using interviews and documentation. By using data analysis techniques, namely descriptive which describes and explains the main topics discussed in this research. Then use conclusion drawing in a deductive manner. The results of this research are that the Religious Affairs Office's efforts in providing services for people with disabilities, namely marriage guidance for people with disabilities, are carried out independently (individually). Because for people with disabilities who are deaf, they need a facilitator in sign language, while for people with disabilities they need a way for wheelchairs and also a special room for people with disabilities and there are also different solutions from each KUA of Palembang City in providing a mechanism for preparing Ijab Qobul for people with disabilities at KUA Palembang City.